A Strategy for Asymmetrical Measures to Reduce Bribery in Bangladesh - Abdullah Al Mahmud; Minhazur Rahman Rezvi (UIN Sunan Gunung Djati, 2022)
Bangladesh is one of the most corrupt countries with a rampant bribery scenario. In the public service sector of this country, service is almost considered to be unattainable without bribing the service providers. From the viewpoint of specialists and ad-hoc academicians, symmetric punishment measure has been a failed mechanism to stop rampant bribery. This study initially pondered the reasoning behind the severity of the bribery scenario in Bangladesh using the dataset of the National Households Survey's 2017 (NHS) of Transparency International Bangladesh (TIB). It analyzed the legal jurisdictions of bribery especially the penal code 1860. In this study, following Basu argument on the asymmetric punishment system (harassment bribe) for India, an asymmetric punishment measure has been proposed through a game theoretical explanation about how it will work for Bangladesh instead of the current symmetric one. This game-theoretical analysis shows that asymmetric punishment is more efficient for reducing rampant bribery in a country than symmetric punishment. The study suggests the government initiate an asymmetric punishment policy on bribery with a strict punitive measure and monitoring of bribe-taking which, with a qualitative approach and case study.